Substitution of waqf: maqasid al-shari'ah and public interest - Awang, Abdul Bari; Amir hamzah, Faiz Sakinah (2018)
The application of waqf property is highly encouraged as it reflects economic growth and development and fulfills the needs of modern society. Therefore, waqf substitution (istibdal) is indispensable in the implementation of waqf, so the waqf property is not being wasted and remains beneficial to society. Although waqf substitution constitutes an important element of the Muslim economy, is has yet to be agreed upon whether it serves necessity (darurah), need (hajah) or embellishment (tahsin). Within the framework of maqasid al-shari’ah, the main purpose of waqf are preserved. This article examines the issues related to the application of waqf substitution, with particular emphasis on its importance in Muslim society as it serves the objectives of Islamic law (maqasid al-shari’ah) and public interest. Key words: Waqf, Substitution, Jurists opinion, Maqasid, Public Interest